Pengembangan bahan ajar e-modul berbasis flipbook pada subtema keunikan daerah tempat tinggalku untuk meningkatkan hasil belajar siswa - Teti Rostikawati Rostikawati (Universitas Sebelas Maret, 2021)
This study aims to develop a flipbook-based e-module as teaching material on the uniqueness of the sub-theme of the area where I live to improve student learning outcomes. The method used in this research is a research and development method with an ADDIE design (Analysis, Design, Development, Implementation, Evaluation). This study was conducted in May-July 2020. The limited study in this study used a single-group pretest-posttest design without using a control class. Based on the results of the validation of the flipbook-based e-module by three validators and two primary school teachers, they were involved to assess the feasibility of the content, language and appearance. The feasibility assessment by experts and teachers uses a validation sheet via google form. The results obtained indicate valid criteria with an achievement rate of 85.7% so that the e-module is feasible to be used in learning. The results of the pre-test and post-test N-gain analysis showed a mean N-gain value of 0.56 with moderate criteria. This shows that the flipbook based e-module produced in this study is considered valid to be used in teaching the uniqueness of the area where I live in primary school.